Detection of Mycobacterium avium subspecies paratuberculosis Formula Milk in Bogor - Widagdo Sri Nugroho; Minarwati Sudarwanto; Denny Widaya Lukman; Ewald Usleber (Jurnal Teknologi dan Industri Pangan, 2008)
Mycobacterium avium subspecies paratuberculosis (MAP) becomes a public health concern in developed countries which is usually associated to Crohn’s disease (CD) in human. The disease shows similarities in clinical signs and pathology characteristic with John’s disease (JD) in ruminants which is infected by MAP. Researchers in Europe, USA, and Australia detected MAP in their dairy products and showed the relationship among MAP, CD, and JD. Meanwhile Indonesia imported milk and milk products from those countries to cover the national demand. This situation keeps MAP as potential-problem in national dairy herd and human health in the future. The aim of this study was to detect MAP in the formula milk for toddler. Fifty samples from five established milk producers were taken on August 2006 at the supermarket in Bogor. Two separate diagnostic methods were used parallel in this study i.e polymerase chain reaction method (PCR) with insertion sequence F 57 as the primer and the Mycobacterial Growth Indicator Tube (MGIT). Neither MAP grew in MGIT after 20 weeks of incubation period but 5 samples were found positive by nested PCR. Although there was no evidence weather MAP grew from the samples, as well as in human to provide data on MAP in Indonesia. Key words: Mycobacterium avium subspecies paratuberculosis, growing up milk formula, PCR F57